Dilema Droit De Suite Untuk Karya Seni Rupa - Radian Suparba (JIPRO: Journal of Intellectual Property, 2019)
Droit de suite is a French term that introduces a law in the sense of the artist's resale right, namely the right granted to artists and their heirs to the resale of their copyrighted works. Then the creator of artworks and his heirs get a part of the return of their works when artworks change ownership through selling. This will bring a balance  for copyright in Indonesia, that gave more attention in music and literature. Because music and literature can bring a passive income for all economic activities through royalty. in otherwise artworks couldn't get passive income, because artists just sell it whatever the price goes to others or buyer. In these days the price of artworks will go high in years after first purchase, it means there is the first buyer that buy artworks in small price, but the first buyer can sell it to the second buyer, the second buyer can sell it to the third buyer and so on with higher price than first purchase. That will trigger some artists or the heir, why can't get anything when the artworks price has gone up, while music and literature have a royalty system. Droit de suite system can be a solution for artists get passive income, but first must through the lawmaker to recognize droit de suite. Droit de suite system, in short, is a passive income system for artworks such as paintings, drawings, carvings, calligraphy, sculpture, sculpture, or collages. This system work when artworks got to sell at a price higher than first selling. as long as artworks still exist the price is going up after years and the ownership of artworks changes. When ownership change by through seller or dealer of artworks, the system will claim the right of artists for resale an artwork to another buyer. That will force a market to give exclusive attention to artworks in Indonesia better than sell it on the street to tourist as souvenir. The basic knowledge of droit de suite is important before lawmakers make a decision to recognize it. So that the lawmakers can make what kind droit de suite that can balance the law f copyright, because each country has diffrent systems but basic still same. There Berne Convention gave the basic system and limitation for droit de suite, so not all artworks gate the right.